Oral care practices in non‐mechanically ventilated intensive care unit patients: An integrative review. Issue 13 (13th March 2019) - Emery, Kimberly Paige; Guido‐Sanz, Frank
Abstract: Aims and objectives: To explore current oral care practices in nonmechanically ventilated ICU patients. Background: Oral hygiene is an important aspect of nursing care in hospitalised populations. Oral care is a disease preventive and cost‐effective measure for patients, particularly in ICU patients. Numerous studies support the value of oral care practices in mechanically ventilated ICU patients. Due to evidence supporting the benefits of oral care in nonmechanically ventilated patients, it would be beneficial to examine the literature for oral care practices in this population. Methodology: Literature searches of the following databases were performed: CINAHL Plus, MEDLINE, PsychInfo, Academic Search Premier, Cochrane Database of Systematic Reviews, and Web of Science. Three peer‐reviewed articles were included in the review after inclusion criteria were applied. Findings were appraised, organised conceptually and synthesised using Torraco (2016b) as a guiding framework. Evidence was appraised using the Johns Hopkins Nursing Evidence‐based Practice Rating Scale. PRISMA reporting guidelines were followed, when applicable. Results: Findings support the existing gap in the literature of oral hygiene practices in nonmechanically ventilated ICU patients. Themes included the type of oral care products used, frequencies of oral care, documented oral care practices and personnel that performed the care. Study implications: This integrative review identified an important gap in the literature for oral care practices in nonmechanically ventilated ICU patient populations. Further research on current oral care practices and development of evidence‐based guidelines for this population are recommended. Relevance to clinical practice: Nurses should provide oral care to all hospitalised patients and follow oral care guidelines specific to their population, if available.